A framework for messy communication: A qualitative study of competing voices of authority on social media - Seth J. Meyer; Kimberly Wiley (Administrative Sciences, 2024)
While governments, nonprofits, and influencers differ dramatically in their resource availability for social media content creation and their duties to public safety, health, and welfare, all play a role in communication with the public at large. Governments provide for the broader public good and nonprofits and influencers have the opportunity to serve isolated communities vulnerable to social ills and health crises. We explore how these three content creator groups concurrently and independently use social media to provide critical information. We qualitatively coded 1392 posts by governments, nonprofits, and influencers on 6 social media platforms shared across the United States during the 2022 Mpox outbreak. We constructed a framework defining a public health communication progression from chaotic to controlled. The findings indicated that governments can reach minoritized communities to resolve a public health crisis by partnering with nonprofits and influencers trusted by these audiences and, most importantly, practicing flexible control over shared messaging.
Keywords: 350; influencers; Monkeypox; Mpox; public communication; public health; qualitative methodology; social media